A model-independent Dalitz plot analysis of B ±→DK ± with D→KS0h+h- (h=π, K) decays and constraints on the CKM angle γ - Aaij, R; Abellan Beteta, C; Adametz, A; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; et al. (2012)
A binned Dalitz plot analysis of B ±→DK ± decays, with D→KS0π+π- and D→KS0K+K-, is performed to measure the CP-violating observables x ± and y ± which are sensitive to the CKM angle γ. The analysis exploits 1.0 fb -1 of data collected by the LHCb experiment. The study makes no model-based assumption on the variation of the strong phase of the D decay amplitude over the Dalitz plot, but uses measurements of this quantity from CLEO-c as input. The values of the parameters are found to be x -=(0.0±4.3±1.5±0.6)×10 -2, y -=(2.7±5.2±0.8±2.3)×10 -2, x +=(-10.3±4.5±1.8±1.4)×10 -2 and y +=(-0.9±3.7±0.8±3.0)×10 -2. The first, second, and third uncertainties are the statistical, the experimental systematic, and the error associated with the precision of the strong-phase parameters measured at CLEO-c, respectively. These results correspond to γ=(44-38+43)°, with a second solution at γ→γ+180°, and r B=0.07±0.04, where r B is the ratio between the suppressed and favoured B decay amplitudes. © 2012 CERN.